A single-centre, observational, retrospective, real-life study evaluating adalimumab biosimilar ABP 501 in the treatment of plaque-type psoriasis and psoriatic arthritis in originator-naïve patients and in patients undergoing non-medical switch from originator. (3rd July 2021) - Giunta, A.; Zangrilli, A.; Bavetta, M.; Manfreda, V.; Pensa, C.; Bianchi, L.
Abstract: Background: ABP 501 is a biosimilar to the anti-tumor necrosis factor-alfa monoclonal antibody adalimumab and despite its effectiveness and safety in the treatment of psoriasis was demonstrated in randomized clinical trials, no real-life data are available, in particular in patients undergoing non-medical switch from originator to biosimilar. Methods: We retrospectively searched our clinical records for all patients receiving ABP 501 between March 10, 2019 and September 7, 2019 at our Department. Therefore, we identified 94 patients, 46 patients underwent non-medical switch from adalimumab reference product to ABP 501. Results: In originator-naïve patients, mean PASI significantly improved from baseline to week 24 ( p < .0001) in both Pso and PsA cohorts. In these patients, mean DAS-28 ESR improved with no significant differences from baseline. In patients undergoing non-medical switch from adalimumab reference product to ABP 501, no significant difference in PASI or DAS-28 ESR were observed from week 16 before switch to week 24 after switch. Conclusions: AB- 501 is an effective treatment for plaque-type psoriasis and psoriatic arthritis regardless if patients are originator-naïve or if they were switched from the reference product.